DETERMINAN KEPATUHAN WAJIB PAJAK UMKM DENGAN VARIABEL PREFERENSI RESIKO DAN VARIABEL KONDISI KEUANGAN SEBAGAI VARIABEL MODERASI (STUDI PADA WAJIB PAJAK UMKM DI KOTA MALANG) - UTOMO, FATHUR RAHMAN (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
This study aims to examine the influence of subjective norms, the attitude of not supporting tax evasion, and perception of the quality of tax service on the compliance of SMEs taxpayer, and the influence moderation of risk preference on the perception relation of the tax service quality with taxpayer compliance, and the influence of the moderation of the financial condition tax service and taxpayer compliance. The object of this research is taxpayers who have SMEs in Malang. This study used the Theory of Planned Behavior (TPB) model, Theory of Prospect (TP), and Alabede et al. (2011). A total of 197 data were collected using survey data with non probability sampling technique. Metohed of data analysis using partial least square in application PLS. Test results show that subjective norm and attitude does not support tax evasion have a positive effect on taxpayer compliance, The effect of moderating risk preference has been shown to improve the relationship between attitude not supporting tax evasion with tax compliance. Meanwhile, the perception of the quality of tax service has a negative effect on taxpayer compliance, so that the condition to test the effect of moderation of financial condition was lost. The implication of this research is the government should pay more attention to the financial condition of the taxpayer who has SMEs so as to minimize the occurrence of tax evasion, it has the possibility of influence over the subjective norm of the taxpayer so that it becomes obedient to the tax regulations.Keywords: taxpayer compliance, Theory of Planned Behavior, moderation of risk preference, moderation of financial condition